9x^2 - 8x - 1 = 0
(9x + 1(x - 1) = 0
x = -1/9 , 1
x intercepts are -1/9 and 1.
Answer:
D
Step-by-step explanation:
A is not, because 2-5x = -5x+2
(nothing has changed but the order)
B is not, because 3-5+2x = 2x-2
because 3-5 = -2. so -2+2x can be rewritten as 2x-2.
C is not, because 5x-2x = 3x
because you combine like terms, and 5-2 is 3
D <em>i</em><em>s</em><em>,</em> because 2x-2+3x = 5x-2
because you combine like terms (2x+3x=5x) and -2 is left.
-10 is the correct answer
Answer:
61,442,669,034
Step-by-step explanation:
Standard form will always be in number form.
Answer:
x is in (0, 17)
Step-by-step explanation:
The compound inequality is ...
0 < x < 17
The "equal to" case is not included on either end, so round brackets are used:
(0, 17)